Time-sensitive networking (TSN) and wireless TSN technology - Fangmin XU; Lijiao WU; Fan YANG; Chenglin ZHAO (Dianxin kexue)
Time-sensitive networking (TSN) provides end-to-end data transmission with extremely low-latency and high-reliability over ethernet,which is suitable for time-sensitive applications,widely used in automatic driving,industry of internet and other scenarios.Firstly,the characteristics of TSN were summarized,the working principles and features of TSN standards were elaborated in detail,the network technology that provided deterministic and reliable data transmission in wireless network was especially introduced,as wireless TSN technology.In addition,the application cases of TSN were briefly analyzed.The challenges and problems of TSN and wireless TSN technology and their application in industrial scenarios were discussed,and the future research directions were prospected.